Strategi Rumah Belajar Merah Putih dalam Menangani Anak dari Pekerja Seks Komersial yang Tidak Sekolah - Astrid Liani Kamal; Budiaman Budiaman; Martini Martini (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
This study aims to describe the strategies implemented by Rumah Belajar Merah Putih in addressing the educational needs of children of commercial sex workers who are not enrolled in formal schooling. A qualitative descriptive approach was used, with data collected through observation, interviews, and documentation. The findings indicate that Rumah Belajar Merah Putih faces several challenges, including limited facilities and infrastructure, insufficient funding, low public awareness of the importance of education, a shortage of qualified teaching staff, and difficulties in establishing external partnerships. To overcome these obstacles, the organization has developed strategies encompassing four key aspects: (1) Corporate strategy, which emphasizes the formulation of a vision, mission, and goals in response to the community’s lack of attention to education; (2) Program strategy, designed based on the background of the learners to raise awareness of the importance of education; (3) Resource support strategy, aimed at addressing the limitations in teaching staff, funding, and facilities; and (4) Institutional strategy, focused on strengthening internal communication and expanding external partnerships to tackle collaboration challenges. These four strategies have proven effective in addressing the identified challenges and serve as a crucial foundation for providing inclusive education for children of commercial sex workers, although continuous improvement and reinforcement are still needed.